Stress and emotion in a locked campus: the moderating effects of resilience and loneliness - Wang, Qiuwen; Yan, Gonggu; Hu, Yueqin; Ding, Geyi; Lai, Yidie (Frontiers in Psychology, 2024)
The aim of this study is to investigate the dynamic relationship between Chinese students’ emotions and stress during a strict lockdown period in a university setting and the context of a global pandemic. Dynamic structural equation modeling was used to investigate the moderating role of resilience and loneliness in this relationship. The participants consisted of 112 students. Based on loneliness and resilience measures and the intensive tracking of emotional stress over a 21-day period, the results of data analysis indicated that the students’ overall levels of positive emotions were low and relatively independent of negative emotions. Negative emotions were significantly autoregressive and their baseline was closely related to the individual’s overall feelings of stress and loneliness levels, fluctuating with feelings of stress. The results confirm the hypothesis that resilience helps to stabilize emotions. Individuals with low resilience may be more emotionally sensitive in confined environments, while receiving social support may help to alleviate low moods.